2019
DOI: 10.14197/atr.2012191212
|View full text |Cite
|
Sign up to set email alerts
|

The New Virtual Crackdown on Sex Workers’ Rights: Perspectives from the United States

Abstract: On 11 April 2018, the Fight Online Sex Trafficking Act (FOSTA) was signed into law in the United States. FOSTA introduced new provisions to amend the Communications Act of 1934 so that websites can be prosecuted if they engage ‘in the promotion or facilitation of prostitution’ or ‘facilitate traffickers in advertising the sale of unlawful sex acts with sex trafficking victims.’ While supporters of the law claim that its aim is to target human traffickers, its text makes no effort to differentiate between traff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 1 publication
(1 reference statement)
0
16
0
Order By: Relevance
“…This impacts third party actors who profit from sex work by, for example, running an establishment, providing security, spotters, etc. [57], or maintaining online advertising platforms, which were directly affected by the 2018 FOSTA-SESTA legislation in the United States [58]. In some contexts, family members and cohabitants can be charged with "living off the proceeds of prostitution" [57].…”
Section: Policy Environmentmentioning
confidence: 99%
“…This impacts third party actors who profit from sex work by, for example, running an establishment, providing security, spotters, etc. [57], or maintaining online advertising platforms, which were directly affected by the 2018 FOSTA-SESTA legislation in the United States [58]. In some contexts, family members and cohabitants can be charged with "living off the proceeds of prostitution" [57].…”
Section: Policy Environmentmentioning
confidence: 99%
“…A broader survey found that a majority of sex workers had recently been subject to threats of violence, exploitation or coercive attempts to obtain free services, some from people attempting to establish themselves as pimps, which some respondents associated directly with the passing of FOSTA-SESTA (Peterson et al , 2019). This aligns with personal accounts of sex workers being compelled to return to using pimps that they had previously found to be unnecessary for conducting their business when it became internet-based (Cole, 2018).…”
Section: Technology Platforms and Transaction Costsmentioning
confidence: 99%
“…With limited access to mainstream financial platforms, many sex workers have resorted to more specialised platforms with much higher transaction fees (Blunt and Wolf, 2020b). Moreover, due to the global reach of Internet platforms, the loss of Backpage and US-based platforms had impacts outside US jurisdictions (Peterson et al , 2019). For example, many sex workers in New Zealand had used Backpage for advertising before it was shutdown.…”
Section: Technology Platforms and Transaction Costsmentioning
confidence: 99%
“…With limited access to mainstream financial platforms, many sex workers have resorted to more specialised platforms with much higher transaction fees (Blunt et al, 2020). Moreover, due to the global reach of Internet platforms, the loss of Backpage and US-based platforms had impacts outside US jurisdictions (Peterson et al, 2019). For example, many sex workers in New Zealand had used Backpage for advertising before it was shutdown.…”
Section: The Consequences Of Suppressionmentioning
confidence: 99%